The Effect Of Repetition Sprint Training Method Combined With The Level Of Physical Fitness Toward The Speed Of 100 Meter Run - Luh Putu Tuti Ariani (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
There are various modern training methods to increase achievement in a 100-meter run. This research used the repetition sprint method. This research aims to find out the effect of the repetition sprint method on the students with high physical fitness towards the speed in the 100-meter run. The method used in this research is the pre-test post-test design. The sample of this research was 15 students of the Sports Training Education Study Program, sport and health faculty of the Ganesha University of Education. These students are those with the highest physical fitness among 90 students in total. The physical fitness test was through a 2.4-kilometer run. The repetition sprint method was applied in 24 meetings, started with a pre-test and ended with a post-test. The data were analyzed by using descriptive statistics and paired sample T-test. The result shows that there is a difference found before and after the training. It is found that there is a 1.15-second increase in the average speed of the 100-meter run from the whole 15 samples. Therefore, it can be concluded that the repetition sprint training method increases the speed in the 100-meter run.